The effect of foot baths on foot pain and leg edema of nursing students during clinical training - Çelik, Sevim; Cerrah, Gülbahar; Gürel, Berşan; Sağlık, Cavide; Albayrak, İrem (Publishing Office of the University of Rzeszow, 2023)
Introduction and aim. Edema and pain may occur in the lower extremities due to the long-term standing work of nursing students and the stress they experience. In this study, the aim was to determine the effect of foot baths applied after clinical practice on foot pain and leg edema in nursing students. Material and methods. This randomized controlled study was carried out with second year nursing students. The intervention group received a foot bath (including immersion in water and massage). No intervention was performed on the control group. The data was collected using a survey form, edema follow-up form, visual analog scale, and foot bath equipment. Results. Edema levels in the right tibia decreased statistically on the 1st and 2nd days after the foot bath compared to the values measured after nurses performed clinical practice, while the edema level in the left tibia decreased significantly in the first and fourth weeks (p<0.05). The right and left foot pain scores in the intervention group increased in the evening of the day after the clinical practice compared to before clinical practice, and pain scores decreased statistically significantly after foot bath (p<0.001). The foot pain scores expressed by the students in the first week increased continuously (p<0.001). Conclusion. The study showed that a foot bath performed after clinical practice were effective for easing foot pain and leg edema.
Study was approved by the University’s Social and Human Sciences Ethics Committee (decision no. 10, dated 18.03.2020).
Keywords: clinical training; foot pain; foot bath; leg edema; massage; nursing student